Fit-for-Purpose Land Administration- Providing Secure Land Rights at Scale. Volume 2: Country Implementation - Enemark, Stig; McLaren, Robin; Lemmen, Christiaan (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue provides an insight, collated from 26 articles, focusing on various aspects of the Fit-For-Purpose Land Administration (FFPLA) concept and its application. It presents some influential and innovative trends and recommendations for designing, implementing, maintaining and further developing Fit-For-Purpose solutions for providing secure land rights at scale. The first group of 14 articles is published in Volume One and discusses various conceptual innovations related to spatial, legal and institutional aspects and its wider applications within land use management. The second group of 12 articles is published in Volume Two and focuses on case studies from various countries throughout the world, providing evidence and lessons learned from the FFPLA implementation process.